HDAC4 mutations cause diabetes and induce β‐cell FoxO1 nuclear exclusion. Issue 5 (9th April 2019) - Gong, Maolian; Yu, Yong; Liang, Lei; Vuralli, Dogus; Froehler, Sebastian; Kuehnen, Peter; Du Bois, Philipp; Zhang, Jingjing; Cao, Aidi; Liu, Yuantao; Hussain, Khalid; Fielitz, Jens; et al.
Abstract: Background: Studying patients with rare Mendelian diabetes has uncovered molecular mechanisms regulating β‐cell pathophysiology. Previous studies have shown that Class IIa histone deacetylases (HDAC4, 5, 7, and 9) modulate mammalian pancreatic endocrine cell function and glucose homeostasis. Methods: We performed exome sequencing in one adolescent nonautoimmune diabetic patient and detected one de novo predicted disease‐causing HDAC4 variant (p.His227Arg). We screened our pediatric diabetes cohort with unknown etiology using Sanger sequencing. In mouse pancreatic β‐cell lines (Min6 and SJ cells), we performed insulin secretion assay and quantitative RT‐PCR to measure the β‐cell function transfected with the detected HDAC4 variants and wild type. We carried out immunostaining and Western blot to investigate if the detected HDAC4 variants affect the cellular translocation and acetylation status of Forkhead box protein O1 (FoxO1) in the pancreatic β‐cells. Results: We discovered three HDAC4 mutations (p.His227Arg, p.Asp234Asn, and p.Glu374Lys) in unrelated individuals who had nonautoimmune diabetes with various degrees of β‐cell loss. In mouse pancreatic β‐cell lines, we found that these three HDAC4 mutations decrease insulin secretion, down‐regulate β‐cell‐specific transcriptional factors, and cause nuclear exclusion of acetylated FoxO1. Conclusion: Mutations in HDAC4 disrupt the deacetylation of FoxO1, subsequently decrease the β‐cell function including insulin secretion, resulting in diabetes. Abstract : We discovered three HDAC4 mutations (p.His227Arg, p.Asp234Asn, and p.Glu374Lys) in unrelated individuals who had nonautoimmune diabetes with various degrees of β‐cell loss. In mouse pancreatic β‐cell lines, we found that these three HDAC4 mutations decrease insulin secretion, down‐regulate β‐cell‐specific transcriptional factors, and cause nuclear exclusion of acetylated FoxO1. Thus, mutations in HDAC4 disrupt the deacetylation of Forkhead box protein O1 (FoxO1), subsequently decrease the β‐cell function including insulin secretion, resulting in diabetes.